Entrepreneurship and social networks in IT sectors: the case of the software industry - Salavisa, I. (2012)
Empirical research has repeatedly confirmed that social networks are important for the creation, survival and growth of new companies. In this article, the leading research questions are: 1) how do networks contribute to the creation of software firms and further development of a competitive IT sector; 2) what is the structure and features of those networks; 3) how have they evolved from the companies’ founding stage to the current period; 4) what resources (scientific and technological knowledge, skills, and others) do entrepreneurs mobilize through their networks. Based on a survey of 13 companies, those research questions have been tested, using a methodology that combines applied statistical techniques and social network analysis. Our results seem to support our research questions. They also show that some companies and research units play a relevant role as brokers in the access of many companies to technological, informational and other resources.L’évidence empirique a montré à plusieurs reprises l’importance des réseaux personnels des entrepreneurs pour la création et la réussite des entreprises. Dans cet article, les questions de recherche fondamentales sont: 1) quel est le rôle des réseaux sociaux dans la création des entreprises du secteur du logiciel pour les télécommunications; 2) quelles sont la structure et les caractéristiques de ces réseaux; 3) quelle a été l’évolution de ces réseaux depuis leur création jusqu’à présent; 4) quelles sont les ressources (connaissances scientifique et technologique, qualifications, etc.) et les sources mobilisées par les entrepreneurs à travers les réseaux. Nous avons procédé au test de nos hypothèses sur un groupe de 13 entreprises du secteur, ayant recours à une méthodologie qui combine les techniques statistiques et l’analyse des réseaux sociaux. Les résultats semblent confirmer nos questions de recherche. Par ailleurs, ils révèlent l’existence de quelques entreprises et organisations de recherche qui assurent un rôle d’intermédiaires, permettant l’accès à nombre d’entreprises aux ressources technologiques et informationnelles fondamentales.